Early Osteogenic Differentiation Stimulation of Dental Pulp Stem Cells by Calcitriol and Curcumin - Mohammad Samiei; Atefeh Abedi; Simin Sharifi; Solmaz Maleki Dizaj (Stem Cells International)
Curcumin, as a natural phenolic substance, is extracted from the rhizome of Curcuma longa (turmeric), which is effective in bone healthfulness. Calcitriol is an effective hormone in regulating bone remodeling and mineral homeostasis and immune response. Mesenchymal stem cells (MSCs) are found in most dental tissues and resemble bone marrow-derived MSCs. In this work, we investigated the effect of combination and individual treatment of curcumin and calcitriol on early osteogenic differentiation of dental pulp stem cells (DPSCs). Early osteogenic differentiation was evaluated and confirmed by the gene expression level of ALP and its activity. Curcumin individually and in combination with calcitriol increased ALP activity and osteoblast-specific mRNA expression of ALP when DPSCs were cultured in an osteogenic medium. Calcitriol alone increased the enzyme more than in combination with curcumin. These findings demonstrate that curcumin can induce early osteogenic differentiation of DPSCs like calcitriol as a potent stimulant of osteogenesis.